Identifying opportunities for peer-assisted learning in speech language therapy clinical education - Hasherah Mohd Ibrahim,; Nurul Atikah Mohd Shafri,; Tai, Joanna (Penerbit Universiti Kebangsaan Malaysia, 2023)
Peer-assisted learning (PAL) is a potential approach for clinical education that can reduce the burden of clinical supervision and enhance learning. This study aims to identify opportunities for PAL through investigating how speech language therapy students perceive and already participate in PAL within a range of clinical practicum settings. The Speech Sciences students across all years at one institution were invited to participate in a cross-sectional survey that was adapted and revised from Tai et al. (2014). Speech Sciences students reported they applied PAL as part of their learning strategy in their clinical practicums, but still relied on supervisors as the main source of. PAL occurred more frequently in contexts where students already had some clinical experience and spent substantial amounts of time together. Students agreed that PAL enhanced their learning and emphasized a few advantages of PAL, such as having the opportunity to share their ideas, experiences, and knowledge, and providing a positive learning environment without pressure. Confidence to provide information or feedback to peers was cited as a shortcoming in PAL. PAL is a viable teaching approach that can be used in speech-language therapy clinical education program to reduce the supervisory burden. The findings from our study show that PAL is largely self-initiated among speech-language therapy students. However, PAL must be tailored to suit different clinical education year levels and clinical settings to benefit. Case discussion may be one area where scaffolded PAL activities could represent a feasible first step to increasing PAL.